2015
DOI: 10.1002/admi.201500181
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Computational Methods Reveal the Evolution of Buried Interfaces during Synthesis of Ferroelectric Thin Films

Abstract: (1 of 10) 1500181 wileyonlinelibrary.com IntroductionFerroelectric thin fi lms have broad application in society ranging from nonvolatile memories to microrobotics and integrated capacitors. As the sizes of devices and the thicknesses of fi lms decrease, the specifi c surface and interfacial areas increase signifi cantly. At these progressively smaller length scales, interfacial phenomena such as interdiffusion and interface reactions are promoted and can have benefi cial or deleterious consequences on the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…The seminal study focused on the orientation of PZT films was investigated by Chen et al., it was reported that the (111)‐oriented PZT films was induced by the formation of PtPb intermetallic phase . However, the recent study have provided a more intuitive evidence for elucidating that (111)‐oriented PZT films nucleates directly on Pt(111) bottom electrode . Our previous studies have indicated that the preferential orientation of PZT film on Pt(111) substrate was induced by the coherent growth of PZT film due to the lattice mismatch between the PZT film and Pt(111) substrate .…”
Section: Resultsmentioning
confidence: 99%
“…The seminal study focused on the orientation of PZT films was investigated by Chen et al., it was reported that the (111)‐oriented PZT films was induced by the formation of PtPb intermetallic phase . However, the recent study have provided a more intuitive evidence for elucidating that (111)‐oriented PZT films nucleates directly on Pt(111) bottom electrode . Our previous studies have indicated that the preferential orientation of PZT film on Pt(111) substrate was induced by the coherent growth of PZT film due to the lattice mismatch between the PZT film and Pt(111) substrate .…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies on Pb‐based ferroelectric thin films showed similar development of a (111) preferred orientation for an annealing temperature above 550°C, which was attributed to heteroepitaxial growth on transient intermetallic Pt 3 Ti . This view was, however, disputed in a more recent study, indicating that perovskite PZT layers grow directly on platinum substrates . The degree of heteroepitaxial growth of perovskite layers can depend on the amount of intermetallic phases on the surface and their exact interaction with the deposited species.…”
Section: Discussionmentioning
confidence: 99%
“…45,46 This view was, however, disputed in a more recent study, indicating that perovskite PZT layers grow directly on platinum substrates. 47 The degree of heteroepitaxial growth of perovskite layers can depend on the amount of intermetallic phases on the surface and their exact interaction with the deposited species. Similar to the growth of Pb-based films, it may be possible that, for BaTiO 3 -BiScO 3 films, transient Pt-Ti and Bi-Pt intermetallic phases are formed at the interface with the bottom electrode.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the work of adhesion of the PZT(111)/Pt(111) and PZT(111)/Pt 3 Pb(111) interfaces was investigated as a function of PZT termination . The results indicated that the interfaces with Ti‐terminated PZT have the lowest relative adhesion energies .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Jones and coworkers utilized in situ X‐ray diffraction to characterize the evolution of PZT during crystallization . They monitored the formation and disappearance of Pt 3 Pb phase at the PZT/Pt interface, a secondary phase that would be undesirable for device functionality . Specifically, Pt 3 Pb was detected during the PZT formation and found to disappear before the PZT was fully crystallized.…”
Section: Introductionmentioning
confidence: 99%